Reactive Ion Etching (RIE) Etched Wet-Silica-On-Silicon Analysis for Fluid Wettability - Noor Aini Hamimah Abd. Rahim (Universiti Malaysia Perlis, 2008)
RIE etched wet silica-on-silicon analysis is more to surface roughness analysis which analysis on silica substrate after plasma etching especially on de-ionized water droplets testing for fluid wettability scope. The thick oxide is needed for RIE purpose and characterized the etching and surface profile using Atomic Force Microscope. The contact angles measurement is required for the wettability analysis thus to characterized the de-ionized water droplets profile using optical inspection. This contact angles must be more than 90° for non-wetting profile or less than 90° for wetting profile. All the entire measurements angles allowed gives the silica substrate surface analysis results that related to RIE etched wet silica-on-silicon analysis. In this project, all the contact angles are wetting profile which is homogeneous types.